ANALISIS SISTEM INSTALASI LISTIK GEDUNG UNTUK MEMINIMALISASI KEBAKARAN DI KOTA BANDUNG - Bambang Nurcahya, Said; Suwastio Cokrodimejo, Hadi (Jurnal Pengabdian Kepada Masyarakat, 2025)
Recently there have been many fires in buildings in the West Java region, which were caused by electrical short circuits. Electrical short circuits can occur if the building's electrical installation does not follow installation standards, or is not maintained by experts in the field of electricity. Throughout 2014 Until 2024 or approximately ten years there have been hundreds of building fires caused by electrical short circuits, in 2024 only, one example of a fire incident at Pasar Baru Trade Center was caused by a short circuit in the basement with a loud explosion sound and The fire immediately spread to several parts around the basement and spread to the upper floors. To anticipate a similar incident, the researchers tried to analyze the installation system in multi-storey buildings in West Java using a computerized methodology for building multi-storey building databases with a census system and interviews with the person in charge of the building, with the aim of ensuring that the electrical installation managed and maintained properly by certified electrical experts. Meanwhile, the target to be achieved is reducing the risk of fires caused by short circuits and reducing fire victims or zero fatalities. Anticipate using an early warning system connected to a database as a follow-up to the next activity.